Analysis of Contact Strength for Nutation Transmission with Conical Movable Teeth by Fractal Theory - Zhu, Lili; Wang, Guangxin; He, Wenjie; Fan, Wenzhong (Recent Patents on Mechanical Engineering, 2020)
Background: Nutation transmission with conical movable teeth is a patent about a new type of spacial movable tooth drive that was developed based on the bevel planetary gear drive with a difference in the number of small teeth. Objective: The aim of this study was to establish the fractal contact model and calculate the contact strength of the center gear in the nutation transmission with conical movable teeth based on the M-B fractal contact theory and also to demonstrate the validity of the present solution by comparing it with the FEM results and the Hertz contact results. Methods: Based on the fractal theory, the relationship between the loads and the area for the tapered roller teeth in contact with the center disk was obtained, and the four basic parameters were simulated to analyze the effect of the fractal contact model in MATLAB. Results: The accuracy of the fractal contact model was verified using numerical simulation and analysis of the relationship diagram for the real contact area and load and the contact area ratio chart with different parameters. Conclusion: Based on the FEM theory, the Hertz elastic contact theory, and the fractal theory, the tooth surface contact strength of the center disk was compared and analyzed, which enabled us to demonstrate the validity of the present solution, and measures were taken to optimize and improve the followup design of the nutation drive.
Keywords: Conical movable teeth